Petro-mechanical analysis of rocks near Lake Bosomtwe: Implications for engineering use - Wilson, Matthew Coffie; Mensah, Emmanuel; Gbemu, Justice Kwaku; Awuni, Gifty; Ayamdoo, Isaac; Djabeng, Juliet Atta (International Journal of Geography and Geology, 2026)
The main purpose of this project is to determine the petro-mechanical characteristics and their implications for engineering use of rocks near Lake Bosomtwe. The study area is at Abonu near Kuntanase in the Bosomtwe District of the Ashanti Region, Ghana. The study area is underlain largely by Paleoproterozoic rocks (phyllites, metagreywackes) and some Neoproterozoic formations (shale), with the metagreywackes dominating (about 90% of encountered rocks). Petrographic analysis was used to establish the mineralogical, textural, and structural characteristics of the rocks of the study area. An unconfined compressive strength (UCS) measurement was conducted on the sampled rocks using Schmidt Hammer Test and Uniaxial Compressive Strength Test. An Imbibition Method was also used to determine the porosity of some of the sampled rocks. Results of the mechanical strength of the metagreywackes produced unconfined compressive strength values ranging from 18 MPa to 71 MPa, with the metagreywackes showing an inverse relationship with grain sizes. All specimens that were analyzed failed under stress by shattering, except specimen GBOO3B, which failed by shearing along a predefined plane of discontinuity. This form of failure explains that the effects of the identified microstructures are not obvious in the intact rock, a property that makes the rocks suitable as aggregates and engineering materials carrying compressive stresses. The analyzed rocks have effective porosities below 2%, making them suitable for use as concrete, ballasts, and embankment aggregates. However, the high silica content makes the rocks unsuitable for asphalt mixtures due to weak bitumen-silica bonds.